2006
DOI: 10.1063/1.2176390
|View full text |Cite
|
Sign up to set email alerts
|

Thin film SmCo magnets for use in electromagnetic microactuators

Abstract: Efficient magnetic microactuators require a deposition and patterning of a permanent magnetic material. A material that can be deposited in the range of up to a couple of 10μm is sputtered SmCo. For the fabrication of magnetic microactuators, alternative substrate materials besides silicon are of great interest. Therefore, alumina-ceramic as well as B270-glass substrates were included in the investigation. A maximum energy product of 90kJ∕m3 was achieved for rather thick layers of 30μm deposited on glass or ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 6 publications
0
35
1
1
Order By: Relevance
“…A comprehensive work published in 2009 by Arnold reviewed the reported literature on microfabricated permanent magnets [103]. Sputtered [104][105][106], electroplated [91,[107][108][109][110] and pulsed-laser [111][112][113] deposited micromagnets have demonstrated excellent magnetic performance at thicknesses up to 100 µm, whereas powder-based fabrication methods facilitate the manufacture of larger structures (up to 1 mm) but with limited properties [114][115][116]. However, the best micromagnets are conventionally deposited rare earth alloys, whose processing unfortunately presents insurmountable challenges that hinder their viability for integration, such as the need for special substrates and high-temperature annealing treatments [103], and exhibit an inconveniently high corrosion rate [117].…”
Section: Excitation Sourcesmentioning
confidence: 99%
“…A comprehensive work published in 2009 by Arnold reviewed the reported literature on microfabricated permanent magnets [103]. Sputtered [104][105][106], electroplated [91,[107][108][109][110] and pulsed-laser [111][112][113] deposited micromagnets have demonstrated excellent magnetic performance at thicknesses up to 100 µm, whereas powder-based fabrication methods facilitate the manufacture of larger structures (up to 1 mm) but with limited properties [114][115][116]. However, the best micromagnets are conventionally deposited rare earth alloys, whose processing unfortunately presents insurmountable challenges that hinder their viability for integration, such as the need for special substrates and high-temperature annealing treatments [103], and exhibit an inconveniently high corrosion rate [117].…”
Section: Excitation Sourcesmentioning
confidence: 99%
“…[1][2][3] Among the various known permanent magnets, lots of attention has been paid to Sm(CoCuFeZr) z magnets in bulk as well as film due to their extraordinary magnetic properties such as high Curie temperature, large coercivity, large energy product (BH max ), considerably high uniaxial anisotropy, etc. The reported hard magnetic properties of Sm(CoCuFeZr) z bulk compound is mainly due to the formation of a three phase cellular microstructure consisting of rhombohedral Fe-rich Sm 2 (Co,Fe) 17 cells, surrounded by a Cu-rich Sm(Co,Cu) 5 cell boundary phase, and superimposed with a Zr-rich lamellae phase.…”
Section: Introductionmentioning
confidence: 99%
“…9 Budde et al reported an increase in etching rate of SmCo from 0.02 µm/min for dry etching to 12.5µm/min for wet etching. 10 A major concern is whether coercivity is altered during structuring. Budde et al referred to the magnetic properties of the nonpatterned films but not to those of the wet etched films, 10 while Wang et al only gave the magnetic properties of films etched at very low rates.…”
Section: Introductionmentioning
confidence: 99%
“…10 A major concern is whether coercivity is altered during structuring. Budde et al referred to the magnetic properties of the nonpatterned films but not to those of the wet etched films, 10 while Wang et al only gave the magnetic properties of films etched at very low rates. 9 Lemke et al reported that no significant change was observed in the coercivity of their patterned NdFeB films, which however, had relatively low coercivities to begin with (0.2 T).…”
Section: Introductionmentioning
confidence: 99%